ANALISIS PESAN DAKWAH PADA FILM AIR MATA DI UJUNG SAJADAH - Afriandi Afriandi; Marhen Marhen (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The main issue addressed in this thesis is the da'wah message found in the film Air Mata Di Ujung Sajadah. The objective of this study is to analyze the semiotics present in the film and then examine it from the perspective of da'wah to determine whether or not it conveys a da'wah message. This research uses a qualitative approach with Barthes' semiotic theory. Roland Barthes' semiotics is applied to analyze signs and how these signs work by considering the denotative and connotative systems found in the Scenes of the film. Data validity in this research is ensured through triangulation techniques, comparing the findings with previous studies related to the raised issues. The results of this study indicate that the denotative meaning reflects how the connotative meaning is formed from each analyzed Scene. Based on the research findings, the film Air Mata Di Ujung Sajadah contains many da'wah messages representing the aspects of aqidah (faith), syariah (Islamic law), and akhlak (morality). The da'wah message of aqidah in this film is related to faith in Allah SWT. The da'wah message of syariah in the film includes messages related to worship, such as prayer, making du'a (supplications), reading the Qur'an, and working diligently. The da'wah message of akhlak is conveyed through forgiveness, honesty, respect, love, sacrifice, politeness, mutual help, and sincerity.